Efektivitas Kebijakan Desentralisasi Fiskal pada Pertumbuhan Ekonomi dan Ketimpangan Pendapatan Antardaerah - Madakarah, Nafiriair Yufan; Makaliwe, Willem A. (Jurnal Manajemen Bisnis dan Keuangan, 2023)
The implementation of fiscal decentralization in Indonesia has been running for more than 20 years. The government implemented fiscal decentralization policies in overcoming development problems. However, its implementation still raises various issues, including the high dependency of regional governments on transfer funds, while the level of corruption in regional heads is relatively high. The research aims to determine the effectiveness of fiscal decentralization policies on economic growth and income inequality using descriptive quantitative analysis, spatial, and panel data regression. Based on the analysis, 4 provinces are considered effective, 16 provinces are quite effective, and 14 provinces are less effective in implementing their fiscal decentralization policies. 20 out of 34 provinces were considered to have been implemented well, so it was concluded that fiscal decentralization policies were generally implemented relatively effectively in 34 provinces. This is evidenced by the regression analysis that balancing funds, DBH, DAU, and DAK have a positive effect on economic growth, while income inequality has a significant negative effect on decreasing the value of the Gini ratio.